2002
DOI: 10.1021/es020621n
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Characteristic Leaching Procedure and Iron Treatment of Brass Foundry Waste

Abstract: The Toxicity Characteristic Leaching Procedure (TCLP) is used by the United States Environmental Protection Agency to determine if wastes contain extractable components subject to hazardous waste regulations. This paper examines the limitations of the TCLP and the way it is used by studying a particular example. Waste casting sand from brass foundries to which iron metal has been added passes the TCLP test but when placed in a landfill for several years may start to leach lead, copper, and zinc. Results of TCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…While not conclusive, the TCLP results suggest that all of the WFSs could potentially leach elevated quantities of one or more of the metals if beneficially used in an unconsolidated manner (e.g., land application, road subbase). However, the TCLP test was designed to assess leaching from mixed industrial and municipal wastes in the presence of organic acids (Kendell 2003). Because the TCLP simulates conditions within an environment (i.e., landfill) that is different from beneficial use scenarios, the values presented in Table 5 are higher than would have been obtained using a non-buffered extractant such as distilled water (Baba and Kaya 2004).…”
Section: Resultsmentioning
confidence: 99%
“…While not conclusive, the TCLP results suggest that all of the WFSs could potentially leach elevated quantities of one or more of the metals if beneficially used in an unconsolidated manner (e.g., land application, road subbase). However, the TCLP test was designed to assess leaching from mixed industrial and municipal wastes in the presence of organic acids (Kendell 2003). Because the TCLP simulates conditions within an environment (i.e., landfill) that is different from beneficial use scenarios, the values presented in Table 5 are higher than would have been obtained using a non-buffered extractant such as distilled water (Baba and Kaya 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Bronze is an alloy consisting mainly of Cu, thus a transfer of Cu from the casting to the sand can be expected. Kendall (2003) found that sand from a brass (alloy high in Cu and similar to bronze) mold contained elevated Cu concentrations. While the maximum Cu concentration in the WFSs was relatively high at 303 mg kg À1 , the 50th and 95th percentile concentrations were 5.6 and 38 mg kg À1 , respectively, indicating that the majority of WFSs are low in Cu (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…For analysis, the cartridges were open, and the cellulose ester filters were transferred to 120 mL Teflon ® flasks together with 5 mL of concentrated HNO 3 . Sample digestion was performed in the CEM MDS 2000 microwave furnace following the parameters described in Table 1.…”
Section: Sampling and Sample Digestionmentioning
confidence: 99%
“…1 Atmospheric particulate matter generated from melting and pouring of brass in industrial foundries are a concern of occupational health to workers in these environments. 2,3 In foundry workplace environments the particulate matter is usually formed by condensation of metallic vapours, followed by oxidation reactions. [4][5][6] Because the smaller particles remain suspended in atmosphere, inhalation is the major path of contamination.…”
Section: Introductionmentioning
confidence: 99%